2021
DOI: 10.1002/asia.202100656
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances of Zinc‐based Antimicrobial Materials

Abstract: Zinc has been widely utilized as an antimicrobial material, often in the form of complexes or zinc oxide nanoparticles. The efficacy of zinc complexes are often due to the synergistic effect of both the zinc ions and the attached organic ligands. In contrast, the nanoparticle effect of ZnO, and the photocatalytic generation of reactive oxygen species (ROS) has been postulated to be the effective mechanism of ZnO as a biocide. Recently, new forms of zinc‐based biocidal materials have been reported with distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…It is commonly accepted that the pH of the infectious wound microenvironment was weakly acidic. , Bacterial pathogens could produce destructive enzymes and toxins, lowering the local pH in the wound microenvironment. The bactericidal activity of ZEM could accredit to the sudden release of zinc ions. , As a result of the release pattern of ZEM shown in Figure k, Zn 2+ released from ZEM increased as the pH of the buffer solution decreased from 7.4 to 6.0. This suggested that the ZEM nanoplatform was capable of detecting the weakly acidic microenvironment of the infectious wound and the low-pH environment initiated a faster release of Zn 2+ from ZEM.…”
Section: Resultsmentioning
confidence: 97%
“…It is commonly accepted that the pH of the infectious wound microenvironment was weakly acidic. , Bacterial pathogens could produce destructive enzymes and toxins, lowering the local pH in the wound microenvironment. The bactericidal activity of ZEM could accredit to the sudden release of zinc ions. , As a result of the release pattern of ZEM shown in Figure k, Zn 2+ released from ZEM increased as the pH of the buffer solution decreased from 7.4 to 6.0. This suggested that the ZEM nanoplatform was capable of detecting the weakly acidic microenvironment of the infectious wound and the low-pH environment initiated a faster release of Zn 2+ from ZEM.…”
Section: Resultsmentioning
confidence: 97%
“…Prior work demonstrated the bacteriocidal effect of phanorods in vitro. Conjugation of Pol-K and Zn 2+ -loading of phanorods (i.e., phanorod-Zn) was expected to increase the antibacterial effect due to the known antimicrobial effects of Zn 2+ . , We first tested the bacteriocidal activity of phanorod-Zn in a suspension of P. aeruginosa cells. Irradiation of phanorods and phanorod-Zn (10 14 particles/mL) by 808 nm near-infrared (NIR) light (0.3 W cm –2 ) for 15 min resulted in an equilibrium bulk temperature of ∼55 °C (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a promising direction is the development of biocidal composite binders, which make it possible to provide long-term volumetric protection of the material from biocorrosion. In accordance with the data [ 13 , 14 ], the use of substances containing copper and zinc makes it possible to ensure the biocidal properties of cement composites, which helps to solve the problem of material destruction due to biocorrosion [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Thus, hydrosilicates of zinc and copper can be a promising additive for the creation of composite binders, since they allow reducing the consumption of cement in the binder and ensuring the biostability of the resulting cement composites.…”
Section: Introductionmentioning
confidence: 80%